French colonial documentary : mythologies of humanitarianism - Bloom, Peter J. (University of Minnesota Press, 2008)
Tracing the visual rhetoric of French colonial humanitarianism, Peter J. Bloom?s unexpected analysis reveals how the project of remaking the colonies in the image of France was integral to its national identity. Bloom focuses on the promotion of French education efforts, hygienic reform, and new agricultural techniques in the colonies as a means of renegotiating the social contract between citizens and the state on an international scale.